How anthropomorphism affects empathy toward robots - Riek, Laurel D.; Rabinowitch, Tal-Chen; Chakrabarti, Bhismadev; Robinson, Peter (2009 4th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2009)
A long-standing question within the robotics community is about the degree of human-likeness robots ought to have when interacting with humans. We explore an unexamined aspect of this problem: how people empathize with robots along the anthropomorphic spectrum. We conducted an experiment that measured how people empathized with robots shown to be experiencing mistreatment by humans. Our results indicate that people empathize more strongly with more human-looking robots and less with mechanical-looking robots.